Mechanosensitive channel MscL induces non-apoptotic cell death and its suppression of tumor growth by ultrasound - Wen, Xiaoxu; Wang, Yingying; Zhu, Zhenya; Guo, Shuangshuang; Qian, Junjie; Zhu, Jinjun; Yang, Zhenni; Qiu, Weibao; Li, Guofeng; Huang, Li; Jiang, Mizu; Tan, Linhua; et al. (Frontiers in Chemistry, 2023)
Mechanosensitive channel of large conductance (MscL) is the most thoroughly studied mechanosensitive channel in prokaryotes. Owing to its small molecular weight, clear mechanical gating mechanism, and nanopore forming ability upon opening, accumulating studies are implemented in regulating cell function by activating mechanosensitive channel of large conductance in mammalian cells. This study aimed to investigate the potentials of mechanosensitive channel of large conductance as a nanomedicine and a mechano-inducer in non-small cell lung cancer (NSCLC) A549 cells from the view of molecular pathways and acoustics. The stable cytoplasmic vacuolization model about NSCLC A549 cells was established via the targeted expression of modified mechanosensitive channel of large conductance channels in different subcellular organelles. Subsequent morphological changes in cellular component and expression levels of cell death markers are analyzed by confocal imaging and western blots. The permeability of mitochondrial inner membrane (MIM) exhibited a vital role in cytoplasmic vacuolization formation. Furthermore, mechanosensitive channel of large conductance channel can be activated by low intensity focused ultrasound (LIFU) in A549 cells, and the suppression of A549 tumors in vivo was achieved by LIFU with sound pressure as low as 0.053 MPa. These findings provide insights into the mechanisms underlying non-apoptotic cell death, and validate the nanochannel-based non-invasive ultrasonic strategy for cancer therapy.